Analisis Sastra Siber pada Cerpen Berjudul Sepotong Senja untuk Pacarku dengan Pendekatan Struktural - Dyvia Saumi Putri; Siti Nurhalimah; Shintia Ananda (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The development of digital technology has given birth to a new form of presentation of literary works, one of which is cyber literature. The short story “Sepotong Senja untuk Pacarku”by Seno Gumira Ajidarma, published on the medium.com site, is an example of how literary works are transformed in digital space, combining visual elements, interactivity, and hypertextuality. This study aims to analyze the short story “Sepotong Senja untuk Pacarku” by Seno Gumira Ajidarma through a structural approach. The method used is a qualitative method with a literature study technique. The results of the analysis show that this short story has a romance theme, uses a forward plot, first-person point of view, a poetic language style using various figures of speech, and a story message about love that encourages actions beyond logic. The main character is depicted as a romantic and unyielding figure. In addition, the presentation in digital media enriches the reader's experience through supporting images, comment features, and intertextual relationships with other short stories. This short story shows the typical characteristics of cyber literature, namely interactivity and intertextuality that allow for the expansion of meaning in the story.